The unusual properties of anisotropic systems of quasiparticles in superfluid ⁴He - Adamenko, I.N.; Nemchenko, K.E.; Slipko, V.A.; Wyatt, A.F.G. (Физика низких температур, 2007)
We discuss a number of unusual phenomena, which have been discovered recently in anisotropic quasiparticle systems in superfluid ⁴He. These include the creation of high-energy phonons by a pulse of low-energy phonons, the suprathermal distribution of high-energy phonons in long phonon pulses, the mesa shape of the angular distribution of low-energy phonons, the creation of a «hot line» when two-phonon pulses cross. The thermodynamic properties of anisotropic quasiparticle systems of He II are derived for all degrees of anisotropy.